The role of ESG principles in attracting foreign investments - Doniyorbek Ruziokhunov (Science and Education, 2025)
Environmental, Social, and Governance (ESG) principles have become a critical factor in global investment decisions. Investors increasingly prioritize sustainability, ethical governance, and social responsibility when allocating capital. This paper examines how strong ESG performance enhances a country's or company's ability to attract foreign direct investment (FDI). Using case studies and comparative analysis, we demonstrate that nations and firms with robust ESG frameworks experience higher investment inflows, reduced risk premiums, and improved long-term financial performance.